6. TREATMENT RESULTS AND SOME FACTORS RELATED TO DEATH AND SEVERE HOSPITALIZATION OF WHITMORE CHILDREN'S PATIENTS AT THE NATIONAL CHILDREN’S HOSPITAL FROM 2017-2023 (Vietnam Journal of Community Medicine, 2025)
Objectives: Evaluate treatment results and some factors related to death and severe hospitalization of Whitmore children’s patients at National Children’s Hospital from 2017 to 2023.Method: Retrospective and prospective descriptive study on 45 children diagnosed with Whitmore treated at the National Children’s Hospital from January 1, 2017 to December 31, 2023.Results: There were 45 Whitmore pediatric patients. The number of pediatric patients ≤ 5 years old is 26 (57.8%); the male/female ratio is 2/1. Empirically correct initial antibiotics were 28.9%. The average inpatient stay was 21 ± 16 days (2-61 days). Surgical intervention was 64.4%, mainly lymph node abscess extraction or surgical drainage to drain lymph node abscess 82.8%. The cure rate was 84.4% (38/45); mortality was 15.6% (7/45), all 7 of these cases were septicemia.  Some factors related to death and serious illness include: male children, age over 5 years old, clinical diseases such as sepsis, septic shock, decreased white blood cell count, decreased platelet count, CRP is over 98 mg/L and the number of specimens isolated in each case is from 2 or more types of samples.Conclusions: Initial antibiotic prescription according to experience in Whitmore pediatric patients is still low. The mortality rate is high, especially in pediatric patients with sepsis and septic shock.
Keywords: Whitmore in children; sepsis; septic shock